The role of human resources management practices in enhancing the level of social responsibility (An exploratory study of the opinions of a sample of workers in the company Hawkari pharmaceuticals and medical supplies in Iraq) - فاروق حكيم نجم; زانا مجيد صادق; احمد محمود الفقي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study aims to identify the role of of human resource management practices and the level of social responsibility in the Iraqi Hawkary company which is engaged in the distribution and marketing of pharmaceutical products, along with to identify the role of (correlation and impact) of the practices of human resources management in enhancing the level of social responsibility. Directed by the built model, two main hypotheses and drives from them sub hypotheses rises, a questionnaire used as a tool to collect data, amd to test hypotheses of study, the researchers relying on a set of statistical methods. 60 questionnaires distributed to the study samle, 51 questionnaires returned, while 44 questionnaires were suitable for analysis. The most result of this study was the following: the level of human resource management practices and social responsibility in Hawkary Company is high. There is a positive correlation between practices of human resource management and enhance the level of social responsibility in Hawkary pharmaceutical company. There is stastically a significant impact of human resource management practices on enhances the level of social responsibility in Hawkary pharmaceutical company. Based on the this results this study recommend to the need for the companies to rely on diverse sources of attraction and selection of professionals, companies should working tokeep excellence human resources and the application of occupational safety measures and develop specific programs to reduce accidents at work and the need for the Department companies activating style human relationships at work and that treats all employees of the company fair and equal manner.